2011
DOI: 10.1038/ejhg.2011.176
|View full text |Cite
|
Sign up to set email alerts
|

Association of TMEM18 variants with BMI and waist circumference in children and correlation of mRNA expression in the PFC with body weight in rats

Abstract: Genome-wide association studies have shown a strong association of single-nucleotide polymorphisms (SNPs) in the near vicinity of the TMEM18 gene. The effects of the TMEM18-associated variants are more readily observed in children. TMEM18 encodes a 3TM protein, which locates to the nuclear membrane. The functional context of TMEM18 and the effects of its associated variants are as of yet undetermined. To further explore the effects of near-TMEM18 variants, we have genotyped two TMEM18-associated SNPs, rs654823… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
3
17
0
4
Order By: Relevance
“…The associations reported herein were directionally consistent with results from GWAS: TMEM18 rs6548238 C‐allele , BDNF rs6265 G‐allele , rs10767664 A‐allele and NEGR1 rs2815752 A‐allele . Regarding BDNF , Zegers et al screened the coding region of the gene and did not find mutations associated with overweight or obesity in children and adolescents .…”
Section: Discussionsupporting
confidence: 85%
“…The associations reported herein were directionally consistent with results from GWAS: TMEM18 rs6548238 C‐allele , BDNF rs6265 G‐allele , rs10767664 A‐allele and NEGR1 rs2815752 A‐allele . Regarding BDNF , Zegers et al screened the coding region of the gene and did not find mutations associated with overweight or obesity in children and adolescents .…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, the methylation levels of TMEM18 promoter were possibly associated with parameters of obesity and fat distribution (Rohde et al 2014). Similar to our study, mRNA expression of TMEM18 was reported to be well correlated with body weight in rats (Rask-Andersen et al 2012) and knockdown of TMEM18 resulted in an obvious reduction in triacylglycerol accumulation and adipocyte differentiation in HPA-v (Bernhard et al 2013). However, Rachel et al reported that loss of Tmem18 in male mice led to an increase in body weight, which was aggravated by high-fat diet and influenced by increased food intake.…”
Section: Discussionsupporting
confidence: 89%
“…This result is much higher than the data for the European population (Frayling et al 2007) as well as for Polish children (OR at age 4-18 years=1.97, 95% CI 1.29-3.00, p=0.002) (Luczynski et al 2012). It seems that it may be related to the age of the studied subjects, as analyses, carried out in various populations, demonstrate that many of the genetic variant know to be associated with BMI have stronger role during childhood and adolescence than during adulthood (e.g., Hardy et al 2010;Graff et al 2012;Rask-Andersen et al 2012). According to the authors, during adulthood, the obesogenic environment may have a relatively higher influence on body weight than the genetic factors.…”
Section: Fig 2 Association Between Bmi Z-scores and Ftomentioning
confidence: 99%